Major phonemic problems of Bangladeshi learners of English: Reasons behind and solutions - Islam, A K M Mazharul (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
The issue of Bangladeshi EFL learners’ phonemic challenges, though not very battered, has been addressed by some researchers at different times. Even after having a prolonged history of learning and teaching and some research in the field, awkward pronunciations and misunderstandings are still prevailing everywhere, from the primary level to tertiary level and beyond. This study is undertaken to heighten the importance of delving deeper into the root causes of phonemic difficulties of the learners and to pinpoint the major problems. To add flesh to the theoretical skeleton of the topic a group of university students was interviewed along with a questionnaire to check their understanding of English phonology along with some other basic questions related to pronunciation. It can firmly be stated that teaching/learning pronunciation and hence starting from the segmental level has never been followed. Like any other country where English is in the status of a second language or foreign language, it is very natural to face difficulties to master the intricate phonemic features of the target language for the learners. Supposedly, it mostly results from the lack of knowledge of phonology and phonetics of the target language and due to the phonemic differences between the first language and the target language. In this study, the focus is kept mainly on the salient phonemic challenges faced by Bangladeshi learners of English. Bringing in the basic ideas of consonant and vowel sounds, the sound production mechanism is shown, and then the differences between the vowels and consonants of two languages are held out. Tracing out the key difficulties, some suggestions are provided. This writing is expected to be of considerable and comprehensive help for the instructors as well as for the interested learners and crucial addition to the literature of the topic.